Cover Image, Volume 115, Number 10, October 2018. Issue 10 (12th October 2018) - Ryu, Kyung Hwan; Sung, Min‐Gyu; Kim, Boeun; Heo, Seongmin; Chang, Yong Keun; Lee, Jay H.
Abstract : The cover image, by Kyung Hwan Ryu et al., is based on the Article A mathematical model of intracellular behavior of microalgae for predicting growth and intracellular components syntheses under nutrient‐replete and ‐deplete conditions, DOI: 10.1002/bit.26744 .